2023
DOI: 10.1097/md.0000000000033748
|View full text |Cite
|
Sign up to set email alerts
|

Research progress of Traditional Chinese Medicine (TCM) in targeting inflammation and lipid metabolism disorder for arteriosclerosis intervention: A review

Abstract: Atherosclerosis (AS) is a chronic disease caused by inflammation and lipid deposition. Immune cells are extensively activated in the lesions, producing excessive pro-inflammatory cytokines, which accompany the entire pathological process of AS. In addition, the accumulation of lipid-mediated lipoproteins under the arterial intima is a crucial event in the development of AS, leading to vascular inflammation. Improving lipid metabolism disorders and inhibiting inflammatory reactions are the primary treatment met… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3

Citation Types

0
3
0

Year Published

2024
2024
2024
2024

Publication Types

Select...
3
1
1

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(3 citation statements)
references
References 95 publications
0
3
0
Order By: Relevance
“…In contrast, Traditional Chinese Medicine (TCM) has a wealth of clinical experience and a deep historical background in the treatment of atherosclerosis. With ongoing research, extensive investigations have been conducted into the mechanisms of action underpinning TCM monomers, specialized Chinese medications, and complex formulations ( 8 ). This has culminated in the incremental elucidation of the active constituents and molecular underpinnings of TCM's therapeutic efficacy in combating atherosclerosis ( 4 ).…”
Section: Introductionmentioning
confidence: 99%
“…In contrast, Traditional Chinese Medicine (TCM) has a wealth of clinical experience and a deep historical background in the treatment of atherosclerosis. With ongoing research, extensive investigations have been conducted into the mechanisms of action underpinning TCM monomers, specialized Chinese medications, and complex formulations ( 8 ). This has culminated in the incremental elucidation of the active constituents and molecular underpinnings of TCM's therapeutic efficacy in combating atherosclerosis ( 4 ).…”
Section: Introductionmentioning
confidence: 99%
“…Due to the decrease in dry matter intake during the transition period, dairy cows undergo a negative energy balance and experience an overload of non-esterified fatty acids (NEFA) in the blood . However, the liver has a limited capacity for NEFA utilization, resulting in incomplete NEFA decomposition and subsequent excessive production of BHBA, ultimately causing ketonemia in dairy cows. Ketosis imposes substantial economic losses on pastures, not only compromising the production performance but also elevating the susceptibility to other diseases, such as abomasal displacement, metritis, and mastitis, thereby augmenting cow culling rates. ,, In Europe, monensin sustained-release capsules can be added to cow feed to prevent ketosis; however, several countries still prohibit the use of monensin in cow feed. , Traditional Chinese medicine is a new preventive approach for treating lipid metabolism disorder, although more research is needed to prove its effect in dairy cows. , Furthermore, while many studies have demonstrated the potential of rumen-protected choline in preventing ketosis in dairy cows, the associated products are expensive and the quality is inconsistent. , Therefore, a search for a green and safe bioactive substance to prevent ketosis in dairy cows has become the focus of current research.…”
Section: Introductionmentioning
confidence: 99%
“…8,9 Traditional Chinese medicine is a new preventive approach for treating lipid metabolism disorder, although more research is needed to prove its effect in dairy cows. 10,11 Furthermore, while many studies have demonstrated the potential of rumen-protected choline in preventing ketosis in dairy cows, the associated products are expensive and the quality is inconsistent. 6,12 Therefore, a search for a green and safe bioactive substance to prevent ketosis in dairy cows has become the focus of current research.…”
Section: ■ Introductionmentioning
confidence: 99%